2011
DOI: 10.1037/a0020999
|View full text |Cite
|
Sign up to set email alerts
|

A differential deficit in time- versus event-based prospective memory in Parkinson's disease.

Abstract: Objective-The aim of the current study was to clarify the nature and extent of impairment in time-versus event-based prospective memory in Parkinson's disease (PD). Prospective memory is thought to involve cognitive processes that are mediated by prefrontal systems and are executive in nature. Given that individuals with PD frequently show executive dysfunction, it is important to determine whether these individuals may have deficits in prospective memory that could impact daily functions, such as taking medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

14
80
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(95 citation statements)
references
References 63 publications
14
80
1
Order By: Relevance
“…As expected, participants showed an overall better PM task performance on tasks with low retrospective memory demands (regular tasks) compared to tasks with high retrospective memory demands (irregular tasks). Furthermore, participants showed better event-than time-based PM, which is in line with a large body of empirical evidence reporting better performances in event-based than in time-based tasks in different populations (e.g., Bastin & Meulemans, 2002;Einstein, McDaniel, Richardson, Guynn, & Cunfer, 1995;Raskin et al, 2011).…”
Section: Discussionsupporting
confidence: 70%
“…As expected, participants showed an overall better PM task performance on tasks with low retrospective memory demands (regular tasks) compared to tasks with high retrospective memory demands (irregular tasks). Furthermore, participants showed better event-than time-based PM, which is in line with a large body of empirical evidence reporting better performances in event-based than in time-based tasks in different populations (e.g., Bastin & Meulemans, 2002;Einstein, McDaniel, Richardson, Guynn, & Cunfer, 1995;Raskin et al, 2011).…”
Section: Discussionsupporting
confidence: 70%
“…Moreover, some studies demonstrated that PD patients have greater difficulty performing PM tasks in which executive functions are particularly stressed, such as time-based versus event-based tasks Katai, Maruyama, Hashimoto, & Ikeda, 2003;Raskin et al, 2011; report divergent results) and non-focal versus focal tasks (Foster, McDaniel, Repovs, & Hershey, 2009). A significant correlation between performance on PM tasks and tests tapping shifting and planning abilities was also reported Costa, Peppe, Brusa, et al, 2008;Kliegel, Phillips, Lemke, & Kopp, 2005;Raskin et al, 2011).…”
Section: Introductionmentioning
confidence: 75%
“…Time-based PM tasks have less salient cues that are hypothesized to require greater strategic attentional monitoring and self-initiated retrieval processes dependent on frontal systems compared to event-based PM tasks, which generally involve more distinctive external cues that signal the appropriate time to perform an intended action (McDaniel & Einstein, 2000). This pattern of disproportionate deficits in time-versus event-based PM has, for example, been demonstrated in patients with PD (e.g., Raskin et al, 2011), wherein time-based tasks also were more strongly correlated with measures of executive dysfunction.…”
Section: Introductionmentioning
confidence: 93%